2005
DOI: 10.1086/427040
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Cytomegalovirus (CMV)–Specific CD4 T Cell Lines Devoid of Alloreactivity, by Use of a Mixture of CMV–Phosphoprotein 65 Peptides for Reconstitution of the T Helper Repertoire

Abstract: By use of a simple procedure, an immunodominant peptide library can generate T cell lines from allodonors, for the perspective reconstitution of the Th repertoire in immunocompromised hemopoietic stem-cell transplant recipients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 61 publications
3
31
0
Order By: Relevance
“…In addition, pp65-specific killing was similar to that demonstrated in T cell lines expanded by repetitive specific stimulation with pp65-transgenic APC. Comparable results were also described by Rauser et al after expansion of selected pp65-specific T cells with autologous PBMC [15]. We also monitored antigen-specific T cells with MHC class I tetramers during the generation process.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…In addition, pp65-specific killing was similar to that demonstrated in T cell lines expanded by repetitive specific stimulation with pp65-transgenic APC. Comparable results were also described by Rauser et al after expansion of selected pp65-specific T cells with autologous PBMC [15]. We also monitored antigen-specific T cells with MHC class I tetramers during the generation process.…”
Section: Discussionsupporting
confidence: 74%
“…Li Pira and Rauser et al generated pp65-specific T cells by repetitively stimulating them with a mixture of previously identified T cell epitopes. This strategy cuts the total number of peptides, but still depends on the knowledge of relevant epitopes [14,15]. For single proteins like pp65, a variety of data on relevant epitopes allow the design of a peptide mixture containing the most relevant candidates.…”
Section: Discussionmentioning
confidence: 99%
“…However, since we started this trial, a recent report has shown that certain CMV peptide pools can be used to raise CMV-specific T cells from different individuals, irrespective of the HLA class haplotype. 40 In conclusion, this paper describes the first use of adoptive immunotherapy for CMV in haploidentical stem-cell transplants and first ever use of adoptive immunotherapy for Aspergillus infection. We achieved rapid pathogen-specific immune recovery associated with significantly reduced rates of CMV reactivation and galactomannan in serum.…”
Section: Discussionmentioning
confidence: 99%
“…Pentamers were from Proimmune, Oxford, United Kingdom. Protein antigens, derived from different opportunistic pathogens or whole inactivated pathogen bodies, have been described previously (6,7,8,9). Pathogens used as whole bodies or pathogens from which proteins were derived included the following: Candida albicans, Aspergillus fumigatus, Aspergillus niger, Cryptococcus neoformans, Toxoplasma gondii, Mycobacterium bovis ("Mycobacterium tuberculosis var.…”
Section: Methodsmentioning
confidence: 99%
“…), cytomegalovirus (CMV), and human immunodeficiency virus type 1 (HIV-1). Peptides were synthesized by INBIOS, Naples, Italy, or by JPT, Berlin, Germany (6,7,8,9). Final antigen concentrations were 10 g/ml for proteins and 1 g/ml for peptides.…”
Section: Methodsmentioning
confidence: 99%